TINJAUAN LITERATUR PERANCANGAN DESAIN APLIKASI ARSIP ELEKTRONIK - Hafizh Rizqi; Isidorus Anung Prabadhi; Galuh Boy Hertantyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Document management in the digital era requires a system that can optimize the archiving process effectively. Various obstacles that arise in the archive management manual develop the development of technology-based systems to meet the needs of modern organizations. Some problems that are often encountered in manual archiving systems include the length of time for recording, data inaccuracy due to limited storage media, and the difficulty of the document search process. This has an impact on decreasing work efficiency and organizational productivity. To overcome these challenges, designing an electronic archive application is the right solution. This application is designed by considering various aspects such as managing incoming and outgoing documents, an integrated search system, and automatic report generation. From a technical perspective, the application uses a database for structured storage, is equipped with a user-friendly interface, and a security system. Through the right development approach and attention to user needs, an electronic archive system can be an effective solution in increasing the productivity and efficiency of organizational document management. This system not only makes staff work easier, but also provides added value to the organization in terms of saving resources and improving service quality.